Spices and garbage two keys to healthy life - Anis Sholihah; Yuni Aulia Agustin; Nada Kutsuma Vacha; Mohammad Alfan Yusuf (University of Merdeka Malang, 2021)
Indonesia is rich in various kinds of spices and its benefits are no doubt, Wadeng Sidayu Gresik Village has the potential for abundant spices but has not been used optimally, especially the COVID-19 pandemic, this healthy drink is one of the solutions to increase the body's immunity. Making healthy drinks from spices is expected to change people's mindset towards a healthy lifestyle supported by a healthy, clean and free environment from waste and pollution, Ngoro Mojokerjo Village is a large industrial center in East Java so that plastic waste is very troubling because from time to time increased. The effort to reduce plastic waste is by using it as a chair at home. The two spice and waste activities in the two villages went through several stages; the first stage was conducting the survey, the second stage was applying for a permit to the local Village Head, the third stage was collecting spices and plastic waste and the fourth stage was training in making drinks, socializing the use of waste and making chairs from plastic waste. The results of the activity were that technology for making and healthy drink products, technology, and chair products from plastic waste, and public awareness not littering increased by 61%.